Панцирные клещи (Acariformes, Oribatei) гнезд птиц на территории Донецкой области - Ярошенко, Н.Н.; Харченко, В.И. (Вестник зоологии, 1972)
In 1970 47 nests of 11 bird species were investigated in the Donetsk region. 7660 various Arthropoda of 16 taxonomic groups were collected. Among them 337 samples (4.40%) of adult beetle mites, 57 samples (0.74%) of their larvae and nymphs. 35 species of beetle nites are established to belong to 25 genera from 22 families. Schelorigates laevigatus (21.66%), Trichoribates trimaculatus (13.95%), Oppia sp. (9.79%), Oppia nova (8.01%), Schloribates latipes (7.72%), Oppia rossica (5.94%) are predominant.